Improvement of pig manure compost lignocellulose degradation, organic matter humification and compost quality with medical stone. (November 2017) - Wang, Quan; Awasthi, Mukesh Kumar; Zhao, Junchao; Ren, Xiuna; Li, Ronghua; Wang, Zhen; Wang, Meijing; Zhang, Zengqiang
Highlights: Medical stone improved organic carbon and lignocellulose degradation. Medical stone could facilitate the humic acid formation and fulvic decomposition. Medical stone could promote the maturity and aromatization of compost. 10.0% medical stone blending compost provided the higher biomass of pakchoi. Abstract: The present study aimed to investigate the effect of different concentrations (0%, 2.5%, 5.0%, 7.5% and 10.0%) of medical stone (MS) on the lignocellulose degradation and organic matter humification during pig manure (PM) composting. The results indicated that the addition of MS drastically promoted the organic carbon and lignin degradation. Compared to the control, the decomposition rate of hemicellulose and cellulose was increased by 9.64–27.08% and 2.11–12.07% in MS added treatments. Meanwhile, MS amendment significantly improved the humification of composting process, and the humic acid contents in MS added treatments were 5.58–9.75% higher than control. The FTIR and synchronous fluorescence spectra indicated that the aromatization of final compost was promoted with increasing the MS amount. In addition, the application of MS blended composts could significantly improve the biomass and chlorophyll content of pachoi ( Brassica chinensis L.). Due to the effective performance of MS, the 10.0% MS was suggested for PM composting.